Factors Influencing Trapping Success of Northern Bobwhites - Adam C. Behney; Joseph M. Wolske; Thomas M. Cucinotta; Carolin Tappe (Wildlife Society Bulletin)
ABSTRACT Capturing animals is a critical component of many ecological research projects. Factors that increase capture success can save time, money, and improve inference. Even though northern bobwhites (Colinus virginianus) are intensively studied, little information exists on factors that influence trapping success. Using baited walk‐in funnel traps during 2019, we examined how putting cover over traps, scraping litter and vegetation under traps, distance to nearest cover, overhead cover, date, time, and weather influenced trapping success of northern bobwhites in northeastern Colorado, USA. We found that cover placed over traps, litter scraped away underneath traps, traps placed closer to cover, and windy days resulted in greater trapping success. These results should enable researchers to be more successful capturing bobwhites and result in larger samples and more precise inference in future studies. © 2020 The Wildlife Society.